Morphological and physiological properties associated with pirimicarb resistance in cotton aphid, aphis gossypii glover [homoptera: aphididae] - Amal H, A. Atta; Rizk, M. M. A.; Darwish, Y. A.; Eraky, S. A. (2011)
The present wolk was carried out to study the toxicity of pirimicarb to Aphis gossypii Glover collected from Assiut and Glover collected from Assiut and insecticide was build up and the two years.selection was carried out through two years..
Includes reference.
Summary in Arabic.
1
Keywords: Cotton -- Diseases and pests -- Control; Aphis gossyppi -- Control; Insecticides -- Toxicology